PERANGKAT PEMBELAJARAN BLENDED LEARNING BERBASIS PROYEK PADA MATERI BENTUK MOLEKUL - Hajrah, Hajrah; Qadar, Riskan; Hartati, Yuli (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This research aims to develop chemical learning tools in the form of RPP, LKPD, Handout, and assessment instruments that are valid, practical, and effective. This research uses research and development design (Research and Development, R &D). The model used in this study is a modification of the 4-D model from four stages to three stages 3-D including the define, design, and development stages proposed by Thiagarajan. RPP, LKPD, handouts, and assessment instrument validation sheets are used to measure the validity of learning devices. Student response questionnaires and observation sheets for the implementation of learning activities are used to measure the practicality of learning devices. Pretest-posttest, N-gain, and effect size tests are used to measure the effectiveness of learning devices. The results showed that learning devices were declared very valid with a percentage of 90%, learning devices were declared practical with a percentage of 83%, effective learning devices to improve learners' learning outcomes based on the results of N-gain calculations by 0.6 meaning that the increase in learners' learning outcomes belonged to moderate categories and effect size calculation results of 2.01 belonged to the category of very effectiveness levels tall.